Perbandingan Hasil Uji Fisis Komposit Polimer Berbasis Perlit Dengan Batu Apung - Pulung Karo Karo (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2013)
Two kinds of polymer composites hava been made from the basic materials: (a) of an epoxy resin with a river sand aggregate which was mixed with a pumice, and (b) of an apoxy resin with a silica sand aggregate which was mixed with perlite. The preparation of samples used the same percentage of weight, and the percentages of epoxy resin with a thinner were varied from 45 gr, 60 gr and 75 gr. Based on the physical comparative test, such as, density, porosity, presure strength, and sound-proof capacity, it is obtained that sample (b) is better than sample (a) if it is used as a construction material. Keywords: pumice, perlite, polymer composites, resin epoxy.